Experimental Study on Shape and Discharge Capacity of Spillway of Yuyang Lake - LI Songping; JIA Wenbo; ZHAO Yuliang; ZHAO Xueping; CAI Yi (Renmin Zhujiang)
According to the actual operation of spillway of Yuyang Lake in Jiyuan City,this paper systematically studies the spillway shape,discharge capacity,flow pattern &velocity,pressure distribution,energy dissipation and scour prevention based on the hydraulic model test,and further optimizes the engineering design through the comparison test of different schemes.The test results show that the discharge capacity can meet the design requirements after the spillway inlet elevation is reduced;and the energy dissipation is improved after the stilling basin is changed from the secondary level to the first level,which can play a good role in protecting the downstream.In view of the phenomenon that the water flows through the top of the wall,reasonable suggestions are put forward to heighten the pier head at the inlet and the wing wall at the downstream of the spillway.